Three-dimensional evaluation of thoracic aorta enlargement and unfolding in hypertensive men using non-contrast computed tomography. - Craiem, Damian (2013)
Aging produces a simultaneous thoracic aorta (TA) enlargement and unfolding. We sought to analyze the impact of hypertension on these geometric changes. Non-contrast computed tomography images were obtained from coronary artery calcium scans, including the entire aortic arch, in 200 normotensive and 200 hypertensive asymptomatic men. An automated algorithm reconstructed the vessel in three-dimensions, estimating orthogonal aortic sections along the whole TA pathway, and calculated several geometric descriptors to assess TA morphology. Hypertensive patients were older with respect to normotensive (P<0.001). Diameter and volume of TA ascending, arch and descending segments were higher in hypertensive patients with respect to normotensive (P<0.001) and differences persisted after adjustment for age. Hypertension produced an accelerated unfolding effect on TA shape. We found increments in aortic arch width (P<0.001), radius of curvature (P<0.001) and area under the arch curve (P<0.01) with a concomitant tortuosity decrease (P<0.05) and no significant change in aortic arch height. Overall, hypertension produced an equivalent effect of 2−7-years of aging. In multivariate analysis adjusted for age and hypertension treatment, diastolic pressure was more associated to TA size and shape changes than systolic pressure. These data suggest that hypertension accelerates TA enlargement and unfolding deformation with respect to the aging effect.